INTEGRASI AGAMA DAN BUDAYA DALAM TRADISI DUL KADIRAN (Studi Deskriptif Pada Masyarakat Desa Wangkal Kecamatan Gading Kabupaten Probolinggo) - Izza, Ismatul (Humanistika : Jurnal Keislaman, 2018)
ABSTRAKIsmatul Izzah, Lecturer of Institute of Islamic Sciences Zainul Hasan (INZAH) Genggong Kraksaan Probolinggo. Research on Dul Kadiran tradition in Wangkal Village of Gading District Probolinggo Regency. This research was conducted in Wangkal Gading Probolinggo. The goal is to know the meaning, traditions and symbols in the event Dul Kadiran. The type and research strategy used by the authors in this research is descriptive qualitative is a study that leads to the detailed description and depth about the portrait condition about what really happened according to what is happening in the field of study. Data collection techniques in this study using interview and observation techniques. Interviews and observations are intended to extract data directly from the resource persons, either with structured or unstructured interviews. The result of the research found that the procession of Dul Kadiran ceremony in Wangkal Village, Gading District, Probolinggo Regency, has religious and spiritual meaning beside it has become a custom and hereditary culture. It can be seen from the meaning and symbols used in the implementation of the ceremony Dul Kadiran. For example, the meaning of Dul Kikut itself is that the children who are prayed to get the ease of God in gaining knowledge, especially in reciting the Quran. This was done by reading the letters of Yasin and Istighosah, then the father of the child prayed to read the letter of Al-Hadid. Every child who started studying the Quran was held selamat dul presence because with the intermediary it can clear the mind so that children more easily and quickly understand about the religious sciences. Symbols used in the ceremony Dul Kadiran for example tumpeng which is covered with banana leaf and inside there is whole chicken, chicken egg, urap-urap whose foliage has also been determined and the good fruit that grows on the ground and that grow in the soil as a complement symbol which has been hereditary carried out by the Society, the meanings contained in the ceremony Dul Kadiran and also the symbols used in the implementation of the ceremony Dul Kadiran can not be separated from the argument of society that states that an object has certain values.Â Keywords: Religion, Culture and Tradition Dul Attendance Ceremony.